Zhuangzi and the Friendship of Non-Friendship - David Chai (Asian Studies)
Bidding farewell to a friend is a moment of change, not in terms of the nature of the friendship, but the proximity of nothingness between oneself and another. Existing studies on friendship in Daoism can be grouped into two broad camps: one favours comparison with notable Western thinkers such as Aristotle and Derrida to establish its ethical ground, while the other favours characterizing it as a shared experience, typically involving death or self-forgetting. This paper takes a different approach by arguing that Daoist friendship does not lie with the physical self or its emotional disposition but the nothingness of the in-between—the domain of the interhuman encounter. Focusing on the Zhuangzi, this paper will also argue that Daoist friendship can be reframed as the friendship of non-friendship.